Case Report: Advanced magnetic resonance imaging findings in two cases of anaplastic papillary glioneuronal tumor: one case with glioblastoma-like progression - Zhang, Yifan; He, Jialin; Xue, Wei; Fang, Jingqin; Du, Xuesong (Frontiers in Oncology, 2025)
Papillary glioneuronal tumors (PGNTs) are classified by the World Health Organization (WHO) as Grade I neoplasms, with only sporadic reports of anaplastic variants demonstrating aggressive clinical behavior and distinct histopathological characteristics. This study presents two cases of anaplastic PGNT, including one that ultimately progressed to glioblastoma (WHO Grade IV). The first case involved a 47-year-old female patient without a history of seizures. Magnetic resonance imaging (MRI) revealed an irregular mass containing multiple cysts and a mural nodule in the left parietal lobe. Histopathological examination confirmed the diagnosis of anaplastic PGNT. Nineteen months later, follow-up brain MRI demonstrated a recurrent mass at the prior surgical site. During the second resection, histological analysis identified glioblastoma arising from the glial component of the original tumor. The second case concerned a 7-year-old boy presenting with progressive headache. MRI showed a solid-cystic mass in the right frontal lobe accompanied by marked peritumoral edema. Postoperative pathological examination revealed anaplastic PGNT with extensive necrosis. MRI characteristics including prominent peritumoral edema, ring-enhancing cyst walls, restricted diffusion, and elevated lipid/lactate peaks may predict the aggressive nature of anaplastic PGNT. Furthermore, this case series suggests that anaplastic PGNTs harbor malignant potential to transform into more aggressive neoplasms.